Mentoring as a potential means to assist consumer representatives contribute effectively to the assessment of health technologies in Australia: a pragmatic review. (20th December 2022) - Walker, Christine; Donovan, Jan; Watson, Jo
Abstract: Objectives: This project was implemented on behalf of the Health Technology Assessment (HTA) Consumer Consultative Committee (CCC) to explore training to support and retain new consumer representatives to participate effectively in HTA committees. These committees are key parts of the Australian Government's health system. Currently, there is no training available to them, specific to their roles in HTA committees. Hypothesizing that mentoring is appropriate, the project team undertook a literature review to identify definitions of mentoring, its benefits, skills requirements, resources, examples of best practice, and how mentoring might support consumer representatives in formal health technology assessment committee structures. Methods: A rapid review was commenced by the project team and fifty-seven articles were identified and read independently. Following discussion, the team revised its approach as there was little evidence to assess and drew upon thirty-five articles where elements of mentoring were described. Discussion was followed by a thematic qualitative analysis exploring mentoring models. Results: The project team agreed that features of mentoring programs were necessary to design a mentoring program under the headings of definitions, mentors' qualities, benefits of training, resources, other considerations, and evaluation . These assist the design of a pilot project to test mentoring's effectiveness. Conclusion: Mentoring may assist consumers working in the health technology area to develop their skills and competencies and contribute to representing the needs of health consumers in the approval of applications. A pilot mentoring program is currently being designed and will run with one mentor and one mentee in an HTA committee.